MENGGUNAKAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH PENGANTAR PENDIDIKAN DI STKIP MUHAMMADIYAH MUARA BUNGO - Apdoludin, Apdoludin; Hakiki, Muhammad (Information Technology Education Department, 2020)
The main problem in this research is that the activities and learning outcomes of students in the introductory course have not reached the predetermined standard. The purpose of this study was to increase the Activities and Learning Outcomes of PGSD STKIP Muhammadiya Muara Bungo. The type of research used is PTK. The research subjects of the first semester students (one) of the 2019/2020 Academic Year, totaling 24 students. Data collection techniques using tests, observation data, activity assessment rubrics. The data analysis technique used is descriptive quantitative and qualitative. The results of the study of learning activities can be increased as evidenced by the cycle I to III category is quite active and cycle IV is active category). The scientific approach can also improve student learning outcomes as evidenced by the increasing learning outcomes from cycle I to IV, starting from 3.46; 3.73; 3,74; and 3.86). Thus the scientific approach can increase the activeness and learning outcomes of students in the Introduction to Education course at the STKIP Muhammadiya Muara Bungo.